2017
DOI: 10.1021/acs.cgd.6b01655
|View full text |Cite
|
Sign up to set email alerts
|

Growth Mechanism of Dendritic Hematite via Hydrolysis of Ferricyanide

Abstract: ABSTRACT:The detailed process of the hydrolysis of ferricyanide into dendritic α-Fe2O3 (hematite) crystals with snowflake-like, feather-like and leaf-like morphologies has been investigated. [Fe(CN)6] 3-anions were found to polymerize into large, disordered soft matter aggregates at an early stage. The nucleation of hematite crystals took place near the surface of these aggregates via further hydrolysis. After the crystals grew to a certain size, branches started to appear. When the concentration of ferricya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…Further research on thinner films (5 nm and 10 nm) showed that the films seem to follow a Pseudo-dendritic growth (Fig. S3 ), which has been already observed in some oxides 65 , 66 and molybdates materials 67 , 68 . Moreover, these studies allowed to determine the coalescence threshold of the films, with a critical thickness of ≈15 ± 3 nm and the similar dendritic behavior in thinner samples.…”
Section: Resultssupporting
confidence: 53%
“…Further research on thinner films (5 nm and 10 nm) showed that the films seem to follow a Pseudo-dendritic growth (Fig. S3 ), which has been already observed in some oxides 65 , 66 and molybdates materials 67 , 68 . Moreover, these studies allowed to determine the coalescence threshold of the films, with a critical thickness of ≈15 ± 3 nm and the similar dendritic behavior in thinner samples.…”
Section: Resultssupporting
confidence: 53%
“…As the temperature increased, the morphology of the dendritic fractals changed continuously from hyperbranched dendrites to slightly branched dendrites and, finally, nanorod-branched dendrites . When the concentration is low, growth was preferentially along six equivalent directions, resulting in a flat snowflake-like shape, while high concentrations led to the growth of selective directions forming a feather-like or leaf-like morphology . These results suggest that more comprehensive information, including the raw materials of the sauce glaze, the detailed operations during the manufacturing and firing processes, the local environment for the nucleation, the primary crystal growth and the branch growth, the temperature and time of different operations, and so on, is needed to investigate the detailed growth mechanism of ε-Fe 2 O 3 crystals in ancient Chinese sauce glaze porcelain.…”
Section: Resultsmentioning
confidence: 92%
“…Although a possible growth process has been proposed, the parameters of each step remain unclear. In recent years, dendritic fractals of several materials have been found and investigated, including Fe, Fe 3 O 4 , α-Fe 2 O 3 , γ-Fe 2 O 3 , Ag dendrites, and dendritic aluminum phosphate crystals. Previous studies have suggested that many factors, such as the type and concentration of the precursor, the reaction temperature and time, and the environment for the crystal growth, could have influenced the morphology of dendritic fractals. Taking the dendritic α-Fe 2 O 3 for an example, the K 3 [Fe­(CN) 6 ] complex plays a crucial role in the formation of dendritic fractal structures .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then the solution was subsequently sealed in an autoclave and maintained at 180 °C for 48 h, followed by cooling down to room temperature gradually. 28 The particles were then dispersed in ethanol, and a small drop of the suspension was deposited onto a graphene thin film-coated 2000 mesh copper grid. When dried in air, it was ready for the electron microscopic analysis.…”
Section: ■ Conclusionmentioning
confidence: 99%